2008
DOI: 10.1373/clinchem.2008.109249
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Matrix Metalloproteinase-7: An Early or Metastatic Marker for Renal Cell Carcinoma?

Abstract: The ability to use DBS to measure ASA protein and activity will simplify procedures for collection, handling, and storage of patient samples. The ease of transporting DBS, combined with the diagnostic sensitivity and specificity of these assays, provide a powerful approach to the diagnosis of MLD. After further investigation and validation, these assays may be used for newborn screening for MLD and other lysosomal storage disorders. Importantly, the inability to differentiate ASA-PD from ASA by the activity as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…In colorimetry, Peng Chen et al demonstrated its use for MMP-7 detection with a detection limit of 0.1µg/mL [28]. However, as MMP physiological concentrations in respective carcinomas are between a few ng/ml to µg/ml [8,9,29,30], this method is not sensitive enough, especially for early stage cancer diagnosis. Furthermore, as there are several types of carcinomas that correlate with multiple MMPs, achieving accurate analysis and diagnosis require monitoring of the concentrations of multiple MMPs level simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…In colorimetry, Peng Chen et al demonstrated its use for MMP-7 detection with a detection limit of 0.1µg/mL [28]. However, as MMP physiological concentrations in respective carcinomas are between a few ng/ml to µg/ml [8,9,29,30], this method is not sensitive enough, especially for early stage cancer diagnosis. Furthermore, as there are several types of carcinomas that correlate with multiple MMPs, achieving accurate analysis and diagnosis require monitoring of the concentrations of multiple MMPs level simultaneously.…”
Section: Introductionmentioning
confidence: 99%